2022
DOI: 10.7759/cureus.27015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Oncological Postoperative Outcomes Following Robotic and Laparoscopic Colorectal Resection for Colorectal Malignancy: A Systematic Review and Meta-Analysis

Abstract: The objective of this systematic review and meta-analysis is to compare the postoperative outcomes of robotic and laparoscopic colorectal resection for colorectal malignancy. We performed a systematic review using a comprehensive search strategy on several electronic databases (PubMed, PubMed Central, Medline, and Google Scholar) in April 2022. Postoperative outcomes of robotic versus laparoscopic surgery for colorectal cancer were compared using 12 end points. Observational studies, randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, previous studies comparing the clinical outcomes of RACS with LACS has not been sufficient to prove the benefits of RACS. Some of previous reviews and meta-analysis included non-randomized and observational studies in the meta-analysis which posed a risk of bias ( 23 , 25 , 38 ). Another meta-analysis included only RCTs, but only six studies was selected, leading to a relatively small number of patients and limited outcomes ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies comparing the clinical outcomes of RACS with LACS has not been sufficient to prove the benefits of RACS. Some of previous reviews and meta-analysis included non-randomized and observational studies in the meta-analysis which posed a risk of bias ( 23 , 25 , 38 ). Another meta-analysis included only RCTs, but only six studies was selected, leading to a relatively small number of patients and limited outcomes ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic reviews and meta-analysis had been performed to compare RACS and LACS.A meta-analysis showed that the two methods had similar clinical outcomes ( 23 ), but other meta-analysis declared that RACS had advantages regarding surgical efficacy and morbidity compared to LACS ( 24 , 25 ). However, due to the shortage of strict inclusion criteria, a large amount of low evidence level RACS studies such as retrospective studies was included in above studies, which might resulted in probably unreliable conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three reviews on colectomy were included [30,31,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Of the twentythree reviews, two were systematic reviews [30,57], eighteen were meta-analyses [31,37,39,40,[42][43][44][45][46][47][49][50][51][52][53]55,56,58], and three were network meta-analyses [41,48,54]. The corrected covered area of the 23 reviews was 2.6% (slight overlap).…”
Section: Colectomymentioning
confidence: 99%
“…Within colectomy, multiple indications for surgery and surgical procedures exist. Regarding the indications for surgery, thirteen reviews included colorectal cancer surgery studies only [30,31,41,[43][44][45][46][47][48]54,55,57,58], two reviews focused on resections indicated by diverticular diseases [39,42], and the remaining seven reviews included studies related to colectomy for any or multiple indications [37,40,[49][50][51][52][53]. As for the surgical procedures themselves, nine studies focused on left or right hemicolectomy [50][51][52][53][54][55][56][57][58], four on total mesorectal excisions [31,[46][47][48], two on complete mesocolic excisions [30,45], three on colorectal resections [41,43,44], two on diverticular resections [39,42], and three on multiple surgical procedures related to the colon [37,40,49]<...…”
Section: Colectomymentioning
confidence: 99%
See 1 more Smart Citation